An Economic and Smart Greenhouse System using Microcontroller for Sustainable Agriculture: A Case Study - Bhandari, Samir Raj (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
The demand of food is continuously increasing as compared to its production due to the rapid urbanization, population growth and climate change. In this scenario, greenhouse is an alternative to maximize the food production without increasing fertile land. The smart greenhouse uses integrated sensor system to control and monitor the environment inside the greenhouse. This research focuses on designing cost effective and automatic parameter monitoring system for existing greenhouses using microcontroller. The research was carried out in two parts, initially, feedbacks regarding the current greenhouse and scopes for automation were collected through field survey with the farmers and later, an experimental model was developed in accordance with the data collection. From the data analysis of field survey, it was found that current greenhouses had problems in effective temperature and irrigation control. Thus, the designed model carries out automatic cooling and irrigation with effective monitoring of this parameter in a display. Furthermore, upon economic analysis, labor cost for monitoring of greenhouse was Rs. 1, 66,860per annum which will be reduced. Meanwhile, discounted payback period analysis showed that initial investment will recover after 2.34 years with the cost for conversion to smart greenhouse at Rs 552 sq. meters.